1996
DOI: 10.1007/bf00607281
|View full text |Cite
|
Sign up to set email alerts
|

CT assessment of orbital volume in late post-traumatic enophthalmos

Abstract: The potential of CT to facilitate preoperative planning of reconstructive maxillofacial surgery by orbital volume quantification was analysed in 11 patients with traumatic enophthalmos as a late sequela of zygomatic fractures. We carried out biplanar CT examination of the orbits, and calculated total orbital and fat volumes for the healthy and enophthalmic sides. Displacement of the orbital floor and lateral wall was present in 11 and 7 cases respectively. Indentation of the medial wall was noted in 9 cases. Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 18 publications
1
19
0
2
Order By: Relevance
“…Numerous studies have reported a wide range of normal values of orbital volumes, which ranged from 21 ml to 30 ml. On average orbital volumes tend to be somewhat higher in males than in females (Deveci et al, 2000;Furuta, 2001;Koppel et al, 2003;Kwon et al, 2010;Manson et al, 1986;Schuknecht et al, 1996). Consistent with the findings of Bentley et al, normal orbital volumes were found preoperatively.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Numerous studies have reported a wide range of normal values of orbital volumes, which ranged from 21 ml to 30 ml. On average orbital volumes tend to be somewhat higher in males than in females (Deveci et al, 2000;Furuta, 2001;Koppel et al, 2003;Kwon et al, 2010;Manson et al, 1986;Schuknecht et al, 1996). Consistent with the findings of Bentley et al, normal orbital volumes were found preoperatively.…”
Section: Discussionsupporting
confidence: 81%
“…Since 1985 different orbital volume measuring techniques have been described using three-dimensional (3D) computed tomography (CT) imaging (Bentley et al, 2002;Bite et al, 1985;Carr et al, 1992;Cooper, 1985;Fan et al, 2003;Furuta, 2001;Koppel et al, 2003;Manson et al, 1986;Schuknecht et al, 1996). A number of studies have shown a strong correlation of these measurements with skull measurements (Acer et al, 2009;Cooper, 1985;Deveci et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…5 Recession of the eyeball is a rather frequent consequence, particularly when fractures of the medial wall occur. Several studies based on CT-2D and 3D scans showed that the average orbital volume is about 28.7 ml in males and 21.6 ml in females 6 , and that in post-traumatic enophthalmos its size increases by an average 12% compared to the contralateral. 7 In fact, a recession of 1 mm of the eyeball corresponds to a volume increase ranging, in vitro, between 2.8% and 5.2%, according to different Authors 8-6 (a volume increase of 1 cm 3 causes, in vivo, an enophthalmos of 0.4-0.8 mm 9-10 ).…”
Section: Introductionmentioning
confidence: 98%
“…Die Vo lu me ner mitt lung der Or bi ta nach der Me tho de der ma nu el len Seg menta ti on wur de be reits von Bite [1], Man son [13], Ra mie ri [20], Schuh knecht [24] und Whi te hou se [26] aus führ lich be schrie ben und de ren Ge nau ig keit mit 98 an ge geben.…”
Section: Abb 7 8 Ab Wei Chung Von Quer Durch Mes Ser Und Hö Hen Derunclassified
“…Wei ter hin bie ten die se Tech ni ken die Mög lich keit ei ner ob jek ti ven Be wertung des tat säch lich er reich ten Er geb nisses hin sicht lich der Pla nung. Or bi ta ana lysen wer den in der Re gel an mul ti pla na ren Com pu ter to mo gram men durch ge führt [6,12,24]. Die in di vi du el le com pu teras sistier te zwei-und drei di men sio na le Or bi taana ly se, die u. a. eine na vi gier ba re stan dardi sier te vir tu el le Pla nung auf der Ba sis eines CT-Da ten sat zes er laubt, ist bis lang nur in Ein zel fäl len ver füg bar [4].…”
unclassified